2002
DOI: 10.1021/jm020241c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure−Activity Relationships of 6,7-Disubstituted 4-Anilinoquinoline-3-carbonitriles. The Design of an Orally Active, Irreversible Inhibitor of the Tyrosine Kinase Activity of the Epidermal Growth Factor Receptor (EGFR) and the Human Epidermal Growth Factor Receptor-2 (HER-2)

Abstract: A series of of 6,7-disubstituted-4-anilinoquinoline-3-carbonitrile derivatives that function as irreversible inhibitors of EGFR and HER-2 kinases have been prepared. These inhibitors have, at the 6-position, butynamide, crotonamide, and methacrylamide Michael acceptors bearing water-solublilizing substituents. These compounds were prepared by acylation of 6-amino-4-(arylamino)quinoline-3-carbonitriles with unsaturated acid chlorides or mixed anhydrides. We performed competitive reactivity studies showing that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
199
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(208 citation statements)
references
References 24 publications
7
199
0
2
Order By: Relevance
“…Because both the C2-C3 and C7-C8 olefins are necessary to observe the levels of toxicity seen for PL, we speculated that multivalency-the ability to interact with multiple cellular targets or a single cellular target at more than one location-might alter toxicity in this system (13)(14)(15)(16). Thus, we synthesized a structurally analogous PL"monomer," "dimer," and "trimer" using a Mitsunobu approach (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because both the C2-C3 and C7-C8 olefins are necessary to observe the levels of toxicity seen for PL, we speculated that multivalency-the ability to interact with multiple cellular targets or a single cellular target at more than one location-might alter toxicity in this system (13)(14)(15)(16). Thus, we synthesized a structurally analogous PL"monomer," "dimer," and "trimer" using a Mitsunobu approach (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…19). HKI-272 was designed using a homology model for the catalytic domain of HER-2 kinase that was built using a combination of two closely related crystal structures as templates, fibroblast growth factor receptor-1 kinase for the NH 2 -terminal lobe and hematopoietic cell kinase for the COOH-terminal lobe (18,21). The core structure of HKI-272 is similar to the structure of EKB-569 but possesses a different anilino headpiece (compare Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such groups are known to be reactive toward sulfhydryl groups. On the basis of the binding model, cysteine-805, located within the catalytic cleft of HER-2, is ideally positioned for covalent interaction with HKI-272 docked in the binding site (18). The binding model, as well as reactivity studies, suggest that the dimethylamino group present at the end of the Michael acceptor group can serve as an intramolecular catalyst for the addition of HKI-272 to the protein, which may accelerate the reaction between the bound drug and the protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This CW molecule bridges the interactions between THR790 and the 3-N atom of quinazoline. Wissner et al tried to replace the water molecule with a 3-cyano group, but they found that the potency was not improved by this substitution [45] . In our docking calculations, the highest TPR 1% All , TPR A 1% , and TPR C 1% values were obtained with the structures in the presence of the water molecule.…”
Section: Conserved Water Moleculementioning
confidence: 99%